Uma sala-de-estar na Cracolândia de São Paulo ou uma heterotopia De Braços Abertos - Oliveira, Lilian Breschigliaro França de (2019)
This dissertation relies Michael Foucault's concept of heterotopia in order to deal with a particular space established on the inside of one of the hotels which made up the housing aparatus of the now extinct municipal program De Braços Abertos, operating from 2013 to 2017 during the adminstration of then mayor Fernando Haddad in the Open Drug Use scene known as Crackolândia Paulistana (São Paulo Crackland). The program, which aimed to make use of the concepts of harm reduction and low threshold and was inspired by international initiatives such as Housing First – concept that deals with the question of housing as the first to be solved for people at risk and homeless – pioneered another perspective for the region on how to work with people who suffer as the result of the intensive use of crack and other drugs. The space in the hotel under discussion, which has been called the sala-de-estar (living room), was consolidated as a space of great importance in the interior of the establishment itself and was established as an environment for coexistence. In addition to creating the possibility of a physical location for the support team to congregate, a space where these workers, together with the residents, were able to construct common ground made it possible to care for the residents. The material serving as a foundation for this analysis consists of a group of daily narratives produced by the researcher while working as a part of the team referenced, participating in establishing the space as a place for daily situations of coexistence and care-taking. The reseach also counts on the transcript of a life story entrusted by one of the residents as part of the bond created through this coexistence. The concept of heterotopia, the foundation for this interpretation, serves as a guide to help see and perceive the functioning and existence of this and other spaces, that are like counterspaces. Isolated and not noticed in the happenings of daily life, it is said that such spaces provide a rigid surrounding for society, much like the sala-de-estar speaks to São Paulo's Crackland, and the societies which create them, beyond the social dynamics in which they are inserted